Resgate da inserção das noções elementares do cálculo (em particular, das noções de limite) durante o ensino médio - Ferreira, Alexandre Maia (2014)
This work is an alternative return of the issues related to Di erential and Integral Calculus approach, intuitive and constructive way, during high school. The development of this material starts with doing historical research on the evolution of the study of limit, derivative and integral, then it is a survey of data between faculty and graduate students about the impacts (advantages/disadvantages) that the transfer of redemption ideals related calculation would provide. In order to justify the proposed restoration, a mapping of the contents that require focus on intuitive notions of calculus in the main textbooks used traditionally in public and private schools capixabas was performed. It was questioned from the grade teachers, the vision of the National Curriculum Parameters (PCN), the core curriculum, the availability of training courses and speci c teaching materials for conducting such an initiative as well as the situation in which you can enter these concepts was evaluated harmlessly and commitment to teaching/learning of students. After analyzing the main issues that require the use of concepts of Calculus, in general, was set up to draft sequence with didactic activities, strategies and methodologies developed and presented in a constructive and intuitive way.